Solution of abel‐type hypergeometric integral equation - Kilbas, A. A.; Raina, R. K.; Saigo, M.; Srivastava, H. M. (Mathematical Modelling and Analysis, 1997)
The paper is devoted to the study of the one‐dimensional integral equation involving the Gauss hypergeometric function in the kernel. The necessary and sufficient conditions for the solvability of such an equation in the space of summable functions are proved and two forms for its solution are given. First Published Online: 14 Oct 2010